Mechanical Integrity Verification of Atmospheric Sump Tanks under Sustained Hydrostatic Loading in Fuel Pipeline Facilities - Farand Putra Hendratmo; Muhammad Ritzky Novhar; Dharu Feby Smaradhana (Universitas Negeri Semarang, 2026)
Atmospheric sump tanks are commonly classified as low pressure equipment; however, when operated under sustained liquid filled conditions, their mechanical integrity may be governed by localized structural mechanisms rather than global shell membrane capacity. This study presents a calculation based mechanical integrity verification of a horizontal atmospheric sump tank subjected to sustained hydrostatic loading. The methodology integrates a hydrostatic pressure model with a specific gravity consistency check derived directly from the applied liquid head, and a component-based capacity evaluation performed using effective corroded thickness. The sustained design pressure (combining atmospheric base and hydrostatic head) is established as 1.135 bar (absolute), while the maximum allowable working pressure (MAWP) is evaluated for shell, heads, and nozzle discontinuities. Results indicate that while the global shell capacity is high, the integrity is governed by nozzle reinforcement limits, yielding a governing MAWP of 2.954 bar (gauge equivalent). Sensitivity analysis on fuel specific gravity demonstrates that reasonable density variations affect pressure demand magnitude but do not alter the governing capacity mechanism. Hydrostatic test pressure is subsequently verified using allowable stress scaling, yielding a test pressure of 3.840 bar. The findings demonstrate that integrity verification of atmospheric sump tanks under sustained hydrostatic loading must prioritize local discontinuity-controlled capacity and physically consistent demand modelling rather than pressure only membrane stress assumptions.